Analysis of the Alterations in Symbiotic Microbiota and Their Correlation with Intestinal Metabolites in Rainbow Trout (Oncorhynchus mykiss) Under Heat Stress Conditions - Changqing Zhou; Fengyuan Ding (Animals)
Global warming represents one of the most pressing environmental challenges to cold-water fish farming. Heat stress markedly alters the mucosal symbiotic microbiota and intestinal microbial metabolites in fish, posing substantial barriers to the healthy artificial breeding of rainbow trout (Oncorhynchus mykiss). However, the relationship between mucosal commensal microbiota, intestinal metabolites, and host environmental adaptability under heat stress remains poorly understood. In this study, rainbow trout reared at optimal temperature (16 °C) served as controls, while those exposed to maximum tolerated temperature (24 °C, 21 d) comprised the heat stress group. Using 16S rRNA amplicon sequencing and ultra-high-performance liquid chromatography–mass spectrometry (UHPLC-MS), we analysed the mucosal commensal microbiota—including gastrointestinal digesta, gastrointestinal mucosa, skin mucus, and gill mucosa—and intestinal metabolites of rainbow trout under heat stress conditions to explore adaptive and regulatory mechanisms. Analysis of microbial composition and diversity revealed that heat stress exerted the greatest impact on the diversity of gill and skin mucus microbiota, followed by gastrointestinal digesta, with relatively minor effects on the gastrointestinal mucosa. At the phylum level, Proteobacteria, Firmicutes, and Bacteroidetes were predominant in the stomach, intestine, and surface mucosa. At the genus level, Acinetobacter showed the greatest increase in abundance in skin and gill mucosa under heat stress, while Enterobacteriaceae exhibited the most pronounced increase in intestinal digesta, gastric digesta, and gastric mucosa. Differential metabolites in the intestinal digesta under heat stress were predominantly enriched in pathways associated with amino acid metabolism, particularly tryptophan metabolism. This study provides a comprehensive characterisation of microbiota and metabolic profile alterations in rainbow trout under heat stress condition, offering a theoretical foundation for understanding the response mechanisms of fish commensal microbiota to thermal stress.